2016
DOI: 10.1039/c6sc00153j
|View full text |Cite
|
Sign up to set email alerts
|

Structure and assembly mechanisms of toxic human islet amyloid polypeptide oligomers associated with copper

Abstract: The molecular interaction of hIAPP with Cu(ii) mediates the formation of off-pathway and toxic oligomers which have small-sized and random coil structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…Cu-induced hIAPP conformers would not only be less likely to form amyloid structures, but could actually promote the formation of off-pathway aggregates that may be more toxic to cells. 17 In summary, our study has revealed structural details of the Cu(II)−hIAPP complex, and it has identified the key residues involved in metal ion coordination. Beyond the anchoring His18 residue, Ser19 and Ser20 also play important roles by providing the deprotonated backbone amides that yield a 3N equatorial coordination mode.…”
Section: Articlementioning
confidence: 81%
See 2 more Smart Citations
“…Cu-induced hIAPP conformers would not only be less likely to form amyloid structures, but could actually promote the formation of off-pathway aggregates that may be more toxic to cells. 17 In summary, our study has revealed structural details of the Cu(II)−hIAPP complex, and it has identified the key residues involved in metal ion coordination. Beyond the anchoring His18 residue, Ser19 and Ser20 also play important roles by providing the deprotonated backbone amides that yield a 3N equatorial coordination mode.…”
Section: Articlementioning
confidence: 81%
“…Indeed, a recent mass spectrometry and molecular dynamics study has determined that Cu(II) binding to hIAPP favors the formation of conformers and oligomeric species that differ from those observed in metal-free hIAPP samples. 17 Metal-induced changes in the folding of hIAPP would impact different properties of this peptide. For instance, many studies have demonstrated that Cu(II) binding to hIAPP protects it from enzymatic degradation by the insulin-degrading enzyme (IDE), particularly in the region around His18.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…A sketch of the process leading to the formation of ProIAPP1-48 and IAPP and of their effect on islet β cells is depicted in Figure 1. It is widely believed that the cytotoxicity of IAPP and ProIAPP1-48 is related to their propensity to form toxic oligomers during the early stages of amyloid formation [4] and it has been suggested that metals and specifically Cu(II) potentiate toxicity through stabilisation of these oligomeric forms [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…[51] Other IM-MS based studies showed that Cu(II) ions bind to the histidine 18 residue of hIAPP, which leads to a stabilization of off-pathway oligomers and to an inhibition of hIAPP fibril formation. [52][53][54] A conformerspecific inhibition for hIAPP aggregation was furthermore reported for the molecules silibinin [55] and insulin [56]. Silibinin exclusively binds to the extended β-hairpin hIAPP monomer (amyloidogenic precursor), and as a result the oligomerization is arrested.…”
Section: Amyloid Inhibitionmentioning
confidence: 89%